2015
DOI: 10.1017/s1041610215000642
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of the cognitive abilities screening instrument–short (CASI-S) in primary care in Brazil

Abstract: The CASI-S can be useful for dementia screening in primary care in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…Besides benefits for physical health and psychological well-being, 33 recent studies have shown that engagement in physical activity can play a key role in relation to cognitive decline and dementia. 8 , 34 Wang et al 15 assessed engagement in AADLs and cognitive decline in 1,463 elderly without cognitive or physical impairment. The sample was followed for a mean of 2.4 years, and a significant relationship between engagement in physical AADLs and lower decline in episodic memory and language was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides benefits for physical health and psychological well-being, 33 recent studies have shown that engagement in physical activity can play a key role in relation to cognitive decline and dementia. 8 , 34 Wang et al 15 assessed engagement in AADLs and cognitive decline in 1,463 elderly without cognitive or physical impairment. The sample was followed for a mean of 2.4 years, and a significant relationship between engagement in physical AADLs and lower decline in episodic memory and language was noted.…”
Section: Discussionmentioning
confidence: 99%
“…In aging, it is necessary to differentiate normal from pathological cognitive decline, as early diagnosis of significant changes in cognitive performance allows better treatment, management and therapeutic planning for the elderly patient and their family members, as well as enabling interventions for prevention and for promotion of mental health in the elderly. 7 , 8 Recent studies have explored the relationship between engagement in advanced activities of daily living (AADLs) and cognitive performance, as a means of favoring successful healthy aging. 9 , 10 AADLs are part of the competencies related to daily functioning, but considered more complex as they depend on motivation and preservation of a group of physical and cognitive competencies enabling independent functioning and social participation in broader settings.…”
Section: Introductionmentioning
confidence: 99%
“…Also discussed in the Cullen et al review, [5] however, was an example of low specificity in some random samples [14]. While there is currently not a significant amount of literature devoted solely to its evaluation relative to the other screening tools discussed, [5,[13][14][15][16] those investigators anticipating the need for cross-cultural applicability may wish to consider utilizing the CASI. It is worth noting that the CASI incorporates elements of the MMSE and the 3MS, thus the convergent validity between these measures can be quite high.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, há quatro estudos realizados com o CASI-S (Damasceno et al, 2005;de Oliveira et al, 2015;Martinelli et al, 2013;Rezende et al, 2013 (Damasceno et al, 2005).…”
Section: Instrumentos De Rastreio Recomendados Para Atenção Primáriaunclassified
“…A nota de corte sugerida para o CASI-S foi diferente da apresentada em outro estudo derivado de amostra parcialmente compartilhada (de Oliveira et al, 2015 (Gibbons et al, 2009;Lin et al, 2012;McCurry et al, 1999) e gênero (McCurry et al, 1999). O estudo brasileiro com o CASI-S (versão reduzida) encontrou correlação positiva com os anos de escolaridade e negativa com a idade (Damasceno et al, 2005).…”
Section: Casi-sunclassified